2011
DOI: 10.1166/jnn.2011.3913
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Lithium in Montmorillonite: A Density Functional Theory (DFT) Study

Abstract: The absorption of lithium in montmorillonite [LiSi8(Al3Mg)O20(OH)4] was investigated using Density Functional Theory (DFT). The final position of lithium after absorption was found to be in good agreement with an experimental observation where lithium atom migrated from the interlayer into the vacant octahedral site of montmorillonite. The lithium absorbed on montmorillonite was held together by a very strong attraction between ions and exhibited an insulating behavior as depicted from the density of states cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
4
18
0
Order By: Relevance
“…As compared with our previous calculation of Li-montmorillonite, it was reported that Li atom can be infiltrate into the alumina octahedral layer by surpassing energy barrier of around 6 eV [3]. However in this calculation, Ca could not infiltrate due to some factors such as ionic radius of the Ca which is relatively larger than Li, the force of repulsion between Ca and H of OH is far greater than the force of attraction, and strong Ca-O and Ca-Al bonds.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…As compared with our previous calculation of Li-montmorillonite, it was reported that Li atom can be infiltrate into the alumina octahedral layer by surpassing energy barrier of around 6 eV [3]. However in this calculation, Ca could not infiltrate due to some factors such as ionic radius of the Ca which is relatively larger than Li, the force of repulsion between Ca and H of OH is far greater than the force of attraction, and strong Ca-O and Ca-Al bonds.…”
Section: Resultssupporting
confidence: 57%
“…The structure of montmorillonite has been defined from our previous works [3,4] and more less similar to our model showed here except that the atomic substitution consist on it are different, therefore, it will not be explained in more detail here. In this study, we theoretically performed simulation of calcium-montmorillonite using the Density Functional Theory (DFT) within Kohn-Sham formula implemented in Vienna Ab initio Simulation Packages (VASP) [5,6] at an absolute zero temperature.…”
Section: Model and Computational Methodsmentioning
confidence: 87%
“…The interlayer spacing of the models of the Na-MMT/drugs systems were analyzed every 50 ps of molecular dynamics in order to obtain the average basal spacing of the molecular systems models. We calculated the interaction energy E interaction in the solid state as the non-bond intermolecular interaction energy using the following equation [ 29 , 30 ]; where E total is the total potential energy of the binary system (Layer1-drug molecule, Layer2-drug molecule) in the Na-MMT/drug complex; E MMT is the total potential energy of the MMT layer and E drug is the total potential energy of the drug in the system. E MMT is the energy of MMT layer in the absence of drug and the Na + , and E drug is the energy of the isolated drug (absence of MMT).…”
Section: Methodsmentioning
confidence: 99%
“…In the case where the Li atom is located at the alumina octahedral layer, the orientation of the OH groups of MMT is changed due to the strong interaction between Li and H atom of the OH groups [13]. However, in the case where the Li atom is located at the MMT surface or in the cavity ditrigonal of silica tetrahedral layers, the OH groups do not change significantly but still perpendicular with the b-axis of this figure instead.…”
Section: Resultsmentioning
confidence: 88%